Nurses' competences in the critical care of children undergoing hematopoietic stem cell transplantation - Marianna Ferreira; Lucila Castanheira Nascimento; Fernanda Titareli Merizio Martins Braga; Fernanda Machado Silva-Rodrigues (Universidade Federal de Goias, 2017)
This is a descriptive study, with qualitative data analysis, in order to identify and analyze the experiences and competencies required by nurses in the care of transplanted child, who demand critical care. Nine nurses were interviewed. We analyzed the data according to the procedures for qualitative content analysis, and then we elaborated the following themes: Critical care to the transplanted child: a double challenge for the nurse; Nurses' competences for the care towards the critically ill child submitted to hematopoietic stem cell transplantation (HSCT). The identified competencies based on scientific knowledge, skills and natural abilities and relate to specific knowledge about pediatric HSCT; technical-scientific, interactive and communication skills; management of material resources and equipment; emotional control, empathy and leadership. Such competences help in the construction of a specific profile for the care offered to this clientele, with a view to therapeutic success.